Building a resistance to ignition testing device for sunglasses and analysing data: a continuing study for sunglasses standards - Renan Magri; Mauro Masili; Fernanda Oliveira Duarte; Liliane Ventura (BioMedical Engineering OnLine, 2017)
Abstract Background Sunglasses popularity skyrocketed since its advent. The ongoing trend led to the creation of standards to protect consumers from injuries and secondary hazards due to spectacles use. In Brazil, the corresponding standard is NBR ISO 12312-1:2015 and since there is no mandatory testing, evaluating sunglasses performance provides an insight into compliance with the standard. In a continuing revision of sunglasses standards requirements, resistance to ignition is one of the concerns, since sunglasses should be protected from burning into flames at a pre-determined temperature, which may protect user of getting their sunglasses into flames if some, cigarette sparks reaches the spectacles, as an example. This paper describes the building of a resistance to ignition system and the results of 410 samples that have been tested accordingly to ISO 12312-1. Methods The procedure is in accordance with the resistance to ignition test. It consists of heating a steel rod to 650 °C and pressing it against the sample surface for 5 s, with a force equivalent to the rod weight. For carrying out the assessments, we have build resistance to ignition testing system and assured the testing requirements of the standard. The apparatus has an electrical furnace with a temperature acquisition circuit and electronic control that maintains the temperature of the steel rod at 650 °C. A linear actuator was designed for the project to drive the steel rod vertically and pressing it against the sunglasses samples. The control system is composed by a Freescale development board FRDM-KL25Z with an ARM Cortex-M0 embedded. We have also provided a LabView PC interface for acquiring, displaying, and storing data as well as added a physical control panel to the equipment for performing the evaluations. We assessed 410 sunglasses frames at the built apparatus, where the 410 lenses came out to be in accordance with the guidelines provided by the ignition to resistance test. Out of the 410 tested frames, 50% were made of polyamide (nylon 12); 10% were made of polyamide (nylon 11, mamona oil); 5% were made of cellulose acetate; 15% were made of ABS and 20% were made of polycarbonate. Out of the 410 tested lenses, 80% were polycarbonate; 2% were polymethyl methacrylate (PMMA); 5% CR-39 (with polarizing filter inside); 12.8% polyamide; 0.2% glass. Results For all the 410 tested spectacles frames and lenses, none burst into flames or continued to melt at the end of the procedure, being in compliance with ISO 12312-1:2013. Conclusions The evidences show that all the tested thermoplastic and thermosetting materials are exceptionally resistant to ignition and all samples assessed comply with the resistance to ignition test. The analysis of the sunglasses made herein assures that most of sunglasses currently available to population are made of safe material.